Chemo-free salvage treatment outperforms traditional chemotherapy in advanced lines of relapsed/refractory subcutaneous panniculitis-like T-cell lymphoma - Chen, Chao; Yin, Jingjing; Duan, Minghui; Wang, Wei; Zhao, Danqing; Wei, Chong; Jia, Congwei; Zhang, Wei; Zhou, Daobin; Zhang, Yan (Frontiers in Immunology, 2024)
IntroductionSubcutaneous panniculitis-like T-cell lymphoma (SPTCL) is a rare subtype of non-Hodgkin lymphoma with a good prognosis, but the optimal treatment for relapsed/refractory (R/R) SPTCL has been rarely discussed.MethodsThis study aims to compare the efficacy of conventional chemotherapy and chemo-free immunomodulatory regimen for R/R SPTCL. We retrospectively reviewed the patients with first relapse or primary refractory SPTCL between September 1997 and October 2020.ResultsA total of 19 patients with R/R SPTCL with a median age of 34 were included. All patient received the first-line chemotherapy-based treatment with a median PFS of 1.8 months. In these patients, 16 received salvage second-line treatment with an ORR of 31.3% and a median TTNT of 3.0 months. 13 of these 16 patients received chemotherapy-based treatment, resulting in a median TTNT of 2.4 months. 2 of these 16 patients received allogeneic hematopoietic stem cell transplantation and achieved long term complete remission (CR). In third-line treatment, 7 patients received chemotherapy-based regimen and 6 received chemo-free regimen such as VRMP (bortezomib, lenadomide and methylprednisolone) regimen and CsA plus IFNα regimen. The median TTNT of chemotherapy and chemo-free group were 3.2 months and not reached, respectively.DiscussionChemo-free group had a better TTNT than chemotherapy group (p=0.007). The use of chemotherapy-free regimens for R/R SPTCL appears promising and warrants further validation.